2018
DOI: 10.1101/343012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late B lymphocyte action in dysfunctional tissue repair following kidney injury and transplantation

Abstract: Abstract:The mechanisms initiating the late immune response to allografts are poorly understood. Through transcriptome analysis of serial protocol biopsies in kidney transplant recipients, we found a tight correlation between the initial response to kidney injury and a late B lymphocyte signature associated with renal dysfunction and fibrosis, suggesting a link between dysfunctional repair and immunoreactivity. To specifically investigate the immunological consequences of dysfunctional repair, we followed the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 64 publications
(48 reference statements)
2
26
0
Order By: Relevance
“…These changes in the relative composition of the B cell compartment could have consequences in the immune response against the allograft, as specific B cell signatures have been associated with transplant tolerance 7 and chronic kidney injury. 27 All kidney recipients in our cohort received the same immunosuppressive maintenance therapy, with tacrolimus, mycophenolate mofetil, and glucocorticoids, which did not allow us to discern the specific effect of each drug on the B cells. However, the decrease in transitional and IL-10 þ Breg cell frequencies post-transplantation is consistent with a Figure 4 | The circulating follicular helper T (cTfh)/interleukin (IL)-10 þ regulatory B (Breg) ratio increased post-transplantation (PosTx), and a higher increase in this ratio preceded biopsy-proven acute rejection (BPAR).…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the relative composition of the B cell compartment could have consequences in the immune response against the allograft, as specific B cell signatures have been associated with transplant tolerance 7 and chronic kidney injury. 27 All kidney recipients in our cohort received the same immunosuppressive maintenance therapy, with tacrolimus, mycophenolate mofetil, and glucocorticoids, which did not allow us to discern the specific effect of each drug on the B cells. However, the decrease in transitional and IL-10 þ Breg cell frequencies post-transplantation is consistent with a Figure 4 | The circulating follicular helper T (cTfh)/interleukin (IL)-10 þ regulatory B (Breg) ratio increased post-transplantation (PosTx), and a higher increase in this ratio preceded biopsy-proven acute rejection (BPAR).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cippa et al . suggested that kidney injury in ischemia/reperfusion injury and transplantation are both mediated by a B‐cell response to dysfunctional tissue repair. Interestingly, patients who developed chronic rejection already showed elevated B‐cell activities and other common gene signatures for acute kidney injury including genes related to fibrosis (e.g., COL1A1, DPT, and MMP7) and inflammation (e.g., CD52, CXCL10, and CCL21).…”
Section: The Role Of B Cells Beyond Antibodymentioning
confidence: 99%
“…In addition, IRI/DGF likely contributes to B cell activation and DSA development in human renal allografts. Cippa et al demonstrated a causal relationship between IRI/DGF and subsequent B cell activation in the allografts 45 . This clearly differed from allografts not experiencing IRI/DGF as no B cell signals were demonstrated on protocol biopsies.…”
Section: Therapeutic Approaches To Treatment Of Amrmentioning
confidence: 99%